Evaluation of some low cost tank sealing techniques for seepage control - Maheshwari, Basanti Lal; Apichart Anukularmphai; Christoph, Ing. Fried; Ohta, Hideki; Belgian Government (Bangkok : Asian Institute of Technology, 1981)
The objective of this study was to evaluate the suitability of some potential low cost tank sealing techniques for seepage control in the laboratory and field. The whole experiment was conducted at ICRISAT, Patancheru, India in Alfisol and Vertisol areas. There were three major treatments, viz., use of soil dispersant (NA2co3), soil cement lining and improvement of soil particle gradation, The use of soil dispersant and the improvement of s oil particle gradation were first tested in the laboratory in a specially designed permeameter. Some of the promising treatments found from the laboratory and the soil cement linin~ were tested under field conditions in small experimental tanks (about 1.3 m capacity). The soil cement lining was observed to be the most effective lining for seepage control from the various treatments tried (seepage rate 8 l/m2/day), In Alfisols, next to soil cement was the lining with red soil +black soil (1:2 ratio by weight). The maximum reduction in seepage in Vertisols was 33% (with lining of black soil+ red soil in 2:1 ratio) when compared with control. It was also found that the problem of cracking of soil cement lining, when exposed to sun, was solved by constructing the lining in blocks (30 cm x 30 cm) and providing a 10 mm space between blocks although asphalt did not satisfactorily remain in the space between blocks. Preliminary cost estimates showed all the linings tried in Alfisols are economically justified when a yield increase due to one 50 mm supplementary irrigation to sorghum and maize at the critical stage of moisture stress and investment made in lining was considered. However, it was not so for any of the lining tried in the Vertisol area.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Tanks -- Linings